(untitled) - Gnap, Jozef; Noga, Michal (Doprava a spoje, 2012)
This article explicates the fact that the composition of traffic flow and especially the proportion of freight transport has a relevant influence on the amount of noise from road traffic in cities. This claim is well founded by the results of the measurements, which are based on the proposed regulatory measures and recommendations to reduce traffic noise in problematic areas.